The Vagueness of Norms on Attempted Cybercrimes in Article 17 Paragraph (2) of Law Number 1 of 2023 concerning the Criminal Code - Rony Wijaya; Evi Retno Wulan (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The development of digital technology has given rise to new forms of crime that are fundamentally different from conventional offenses. This study examines the normative ambiguity surrounding attempted offenses in cybercrimes under Law Number 1 of 2023 concerning the Criminal Code (the New Criminal Code/New KUHP) and the Electronic Information and Transactions Law (the EIT Law/UU ITE). Article 17 Paragraph (1) of the New Criminal Code stipulates that for an attempt to be punishable, there must be intent, the commencement of execution, and the non-completion of the act due to circumstances independent of the perpetrator’s will. However, this concept was constructed upon the paradigm of conventional crime, which is physical and linear. Consequently, it creates serious complications when applied to cybercrimes that are virtual, automated, and simultaneous in nature. Furthermore, the formal offense characteristics found in several articles of the EIT Law logically clash with the doctrine of criminal attempt, which inherently requires the non-completion of an act. Using a normative legal research method, this study demonstrates that the phrase